First-Principles Study of the Quasi-Particle and Excitonic Effect in o-BC2N: The GW + BSE Study - Genene Shiferaw Aga; Pooran Singh; Chernet Amente Geffe (Advances in Condensed Matter Physics)
Ternary boron-carbon-nitride compounds are the hardest, chemically stable, and most applicable semiconductors in optoelectronic devices. We investigate the quasi-particle and excitonic properties of type II o-BC2N using many-body perturbation theory (MBPT). The state-of-the-art GW and BSE methods were used to determine the accurate band gap and excited-state characteristics of this material. We simulate the convergence test and structural optimization in DFT, which is the starting point for the GW calculation. We also compute the convergence test of the parameters in GW and BSE. As a result, the bandgap of our system is found to be 2.31 eV and 1.95 eV using the GW approximation and DFT-PBE, respectively. Since the valence and conduction band edges are located at different Brillouin zones, we decide that o-BC2N is an indirect bandgap semiconductor. In addition, by applying the scissor operator, we corrected the quasi-particle bandgap, which shows almost the same result as the GW approximation. Furthermore, using the BSE algorithm, we calculate the optical bandgap of type II o-BC2N to be 4.0 eV with the excitonic effect and 4.4 eV without the excitonic effect. The highest peaks of the imaginary dielectric function with the excitonic effect shift to a lower energy level at 11 eV than without the excitonic effect at 13.5 eV. The electron charge distribution is computed by fixing the hole position. Finally, we suggest that type II o-BC2N is promising for the application of optoelectronic semiconductors.